NC-Clustering demonstrates heterospecificity of the cryptic ant species Temnothorax luteus (FOREL, 1874) and T. racovitzai (BONDROIT, 1918) (Hymenoptera: Formicidae). - Seifert, Bernhard; Csösz, Sandor; Schulz, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 2014)
Evidence is presented that the W Mediterranean cryptic ant species Temnothorax luteus (Forel, 1874) and T. racovitzai (Bondroit, 1918) are clearly separable by exploratory and hypothesis-driven data analyses of complex morphological data sets. Investigation was concentrated to the sympatric range of both species. 18 morphological characters were evaluated in a total of 178 workers originating from 64 nest samples. Classifications by hierarchical NC-Ward clustering, non-hierarchical NC-K-Means clustering, NC-NMDS-K-Means clustering and linear discriminant analysis coincided by 100 % after reduction of the character set to the seven most discriminative characters. The type series of T. massiliensis (Bondroit, 1918) and T. racovitzai (Bondroit, 1918) were assigned to the same cluster with posterior probabilities of p = 1.000 in the former and p = 0.9992 in the latter. The type series of T. tristis (Bondroit, 1918) and T. luteus were allocated to another, clearly separated cluster with p = 0.9999 in each case. Accordingly, T. tristis is considered as junior synonym of T. luteus whereas T. massiliensis was established as junior synonym of T. racovitzai. The classification error of the LDA was 1.7 % in 178 individuals. Despite a broad sympatric range, there are no suggestions to any nest samples containing a mixture of both phenotypes. This rejects the hypothesis that T. luteus and T. racovitzai could represent an intraspecific dimorphism. Significant interspecific differences of the two species in geographic distribution and thermal niche were demonstrated. Mean air temperature from May to August of 24 sampling sites of T. luteus was by 3.77°C cooler than in 21 sites of T. racovitzai (p